A southern Portuguese Margin Perspective of Marine Isotope Stage 47—An interglacial in the 41 kyr World - Voelker, Antje; Rodrigues, Teresa; Trotta, Samanta; Marino, Maria; Kuhnert, Henning (Atmosphere, 2022)
In order to better understand interglacial climate variability within the 41 kyr world, we produced high-resolution climate records for interglacial Marine Isotope Stage (MIS) 47 (1424-1452 ka) at IODP Site U1387 (36 degrees 48 ' N, 7 degrees 43 ' W) on the southern Portuguese margin. Using benthic and planktonic foraminifera stable isotope records, U-37(k') sea-surface temperature (SST), and plankton assemblage data we investigated Mediterranean Outflow Water (MOW) and surface water conditions. The MOW-level records indicate a poorly ventilated and sluggish bottom current during the MIS 48/MIS 47 transition in association with the insolation maximum, whereas a well-ventilated MOW formed a contourite layer during the second insolation maximum. The benthic delta O-18 record shows a fairly abrupt change during the deglaciation of MIS 48, while the surface waters experienced a terminal stadial event that was associated with initial cooling and freshening followed by stepwise warming until interglacial SST was reached at 1450 ka. Interglacial conditions with SST of 24 degrees C or higher persisted until 1427 ka, although warm SST prevailed into MIS 46. The persistent and prolonged warmth is attributed to a northward expansion of the subtropical gyre during MIS 47 as reflected by the dominance of subtropical-tropical planktonic foraminifera species and the presence of warm water coccolithophores taxa. info:eu-repo/semantics/publishedVersion